Perancangan Interior Wardah Beauty House di Surabaya - Viviyenlii Viviyenlii; Sriti Mayang Sari; Celline Junica Pradjonggo (Intra, 2019)
The The tight schedule of activities and daily routines makes people easy to feel tired, bored, and stressed so that they can reduce work productivity. To treat fatigue, boredom, and stress, people often visit the body's beauty and relaxation center to get treatment so that in the future they can be more productive at work. In addition to treating fatigue, boredom and stress, the goal of the community to visit the body's beauty and relaxation center is to beautify themselves, relax the body and pamper themselves.  The purpose of this design is to be able to answer the needs of the community in Surabaya to get body beauty and relaxation facilities in one place. So that people can release fatigue, boredom and stress due to daily routines and their needs can be fulfilled effectively and efficiently. The facilities that will be provided in this design are facial care, body care, hair care, make-up, hair care, and retail areas that sell Wardah products. This design’s concept is Earth, Love, Life. That concept shows the natural impression of the earth with a relaxing feel so that visitors can release fatigue comfortably. This design also wants to help improve people's views about local beauty brands to be more attractive to the wider community.